Oz. The complete sixth season [videorecording (DVD)] - Fontana, Tom, 1951-; Simmons, J. K.; Hudson, Ernie; Akinnuoye-Agbaje, Adewale, 1967-; Wong, B. D.; Walker, Eamonn (Home Box Office ; Distributed by Warner Home Video, 2006)
In this final season of Oz, Schillinger has revenge on his mind, Cyril is facing execution, Beecher is hoping for parole, and McManus is finding solace in a meditative maze. The Oz players rehearse for their presentation of Macbeth and the final act.